2022
DOI: 10.3390/cancers14164021
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Cancers in Adults: A Review of Epidemiology, Supportive Care Needs and Future Research Priorities

Abstract: Rising incidence of specific types of early-age onset cancers in adults aged 18–49 years has been reported in high-income countries. In this review, we summarise the epidemiology of early-onset cancers using exemplar data from a high-income UK region, discuss supportive care needs for young patients and outline future research directions. The incidence rate of early-onset cancers increased by 20.5% from 1993 to 2019 in Northern Ireland. Differences in types of cancer were observed between sexes and across age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 73 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…In addition, the disease and treatments used can leave patients with sequelae that require health systems to provide appropriate resources for their care. 3 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the disease and treatments used can leave patients with sequelae that require health systems to provide appropriate resources for their care. 3 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…As a result of these gaps, delays in the diagnostic process are common [ 24 ]. To address this challenge, it is necessary to promote the collection of family history (CRC and polyps) in primary care, especially amongst younger adults, to better inform screening and referral for risk assessment [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Martinez et al (2019) found that clinical distress related to unmet psychological needs affects one in four women. Focus groups, Social media can be used for patient support, advocacy, and information sharing [19]. Also, participants identified information needs as critical needs.…”
Section: Discussionmentioning
confidence: 99%